AN ANALYSIS OF THE NOUN PHRASE AND THE VERB PHRASE PRODUCED IN “LOVE ME LIKE YOU DO” SONG - Reza Fandana; Ina Rohiyatussakinah (FKIP, Universitas Banten Jaya, 2023)
This article dealt with the noun phrase and the verb phrase in the song entitled love me like you do. In this research the writers used qualitative research since the writers will deal with a case study of syntax and the data will be in the form of phrases. The data will be taken as utterances produced in this song. The writers analyze the data, which consists of four stages classifying stage, analyzing stage, evaluating stage, and conclusion stage. The results of the research are 16 noun phrases and 9 verb phrases has been founded